Intervention hangovers in stabilisation operations: Case studies from Afghanistan and Iraq - Christian Dennys; Ann M. Fitz-Gerald (Danish Institute for International Studies (DIIS), 2011)
This paper argues that the emergence of stabilisation as a concept out of peace-building, state-building and counter-insurgency theories has carried with it some of the key weaknesses of international intervention, in particular the idea that imposing western liberal systems on non-western societies will contribute towards stability. With reference to two case studies, the Wheat Seed project in Afghanistan and a gas cylinder distribution project in Iraq, the paper argues that stabilisation activities do not engage fully with the underlying premise that stabilisation must support and engender local political legitimacy, in part because of the conceptual baggage that stabilisation has adopted from other areas. The paper concludes by arguing that greater use should be made of the knowledge and histories of non-western state formation, characterized as being non-Weberian, as a counter to the overuse by interveners of the desire to support rational Weberian state structures in other countries.
Keywords: 300; Friedenssicherung; Entwicklungshilfe; Politisches Ziel; Afghanistan; Irak